2022
DOI: 10.3390/fermentation8120724
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of New Breed Purple Wheat (8526-2 and 8529-1) Varieties Wholemeal Flour and Sourdough to Quality Parameters and Acrylamide Formation in Wheat Bread

Abstract: The aim of this study was to evaluate the influence of purple wheat (varieties 8526-2 and 8529-1) wholemeal flour (PWWF) left untreated or fermented with Lactiplantibacillus plantarum No. 135 on the quality parameters of and acrylamide formation in wheat bread. Different quantities (5, 10, 15, and 20%) of PWWF were tested for bread preparation. Acidity, colour characteristics, hardness, enzyme activities, and antioxidant activity of PWWF, as well as bread quality and acrylamide concentration, were analysed. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…For example, the fermentation of purple wheat with Lactiplantibacillus plantarum No. 35 resulted in improved DPPH free radical scavenging capacity, and it has been recommended for acrylamide reduction in bread [ 41 ]. Thus, the application of the sourdough processing technique could be an effective method to protect anthocyanins and other phenolic compounds during the production of fermented baked products from colored wheats.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
“…For example, the fermentation of purple wheat with Lactiplantibacillus plantarum No. 35 resulted in improved DPPH free radical scavenging capacity, and it has been recommended for acrylamide reduction in bread [ 41 ]. Thus, the application of the sourdough processing technique could be an effective method to protect anthocyanins and other phenolic compounds during the production of fermented baked products from colored wheats.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
“…Moreover, our previous studies showed that, on the one hand, there are many advantages of adding scalded flour to the main bread formula, however, on the other hand, it can also lead to higher acrylamide (AA) concentration in the final bread (5,6,9). AA is present in heat-processed foods (e.g., potatoes, rice, cereal products, fruits, vegetables, meat, fish, nuts, cocoa-based products, and coffee) at various concentrations (5,6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Acrylamide is a Group 2A-probable human carcinogen (27), therefore the development and application of mitigation strategies are very important, especially in popular food products such as bread (28).…”
Section: Introductionmentioning
confidence: 99%
“…Psyllium (Plantago ovata) plant grows in most parts of the world (15,16) and its health benefits are widely recognized (35)(36)(37)(38)(39)(40)(41)(42)(43). The soluble and insoluble dietary fiber of psyllium husk possesses very good gel-forming and high water absorption ability capacities (44, 45).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, certain lactic acid bacteria are used for the preparation of sourdough-based products. They exert a positive effect on dough rising, which is comparable to that of the baker’s yeast, and the metabolites produced during the fermentation have an important role in the formation of a specific taste and aroma of the bakery products [ 24 , 25 , 26 , 27 , 28 ]. Homofermentative LAB produce lactic acid as a major final metabolite, whereas heterofermentative LAB release lactic acid, acetic acid or ethanol, and carbon dioxide during fermentation, which increases the loaf volume of the bread.…”
Section: Introductionmentioning
confidence: 99%